Catherine the Great: Coleridge, Byron, and Erotic Politics on the Eastern Front - Taylor, Anya (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
Catherine II of Russia, a glamorous, enlightened Romanticist figure in her own right, enraged both Coleridge and Byron. Coleridge, who reported her bloody campaigns in The Watchman, cursed her cruelty at the battle of Ismail in “Ode on the Departing Year” just as she was dying. Twenty-seven years after her death, Byron, in Don Juan cantos 6 to 10, which cover the Russian wars and the St. Petersburg court, attacked her even more vituperatively. Thus, Coleridge’s decision not to be a “Historiographer of Hell” is taken up by Byron in his decision to be that historiographer. The two poets’ responses to Catherine’s brutality and sexuality are intertwined. At the basis of their anger is Catherine’s use of human persons as things. Both show their disgust by reducing the Tzarina to her sexual body, vindictively turning her into a “thing” through rhetorical plays on her body parts.